HUBUNGAN ANTARA KEBIASAAN BELAJAR DENGAN HASIL BELAJAR KOREOGRAFI TUNGGAL PADA MATA KULIAH KOREORAFI TRADISI DI PROGRAM STUDI PENDIDIKAN TARI UNIVERSITAS LAMPUNG - Amanda Putri Sanu, Arista; Ayu Mariana Devi Lestari, Goesthy; Wendhaningsih, Susi (STKIP Subang, 2026)
This study was motivated by a phenomenon that occurred among students of the 2022 cohort in the Dance Education Study Program in the Traditional Choreography course. During the learning process, the lecturer rescheduled the Midterm Examination (UTS) to the end of the semester because, in the first eight meetings, students’ progress in mastering the Single Choreography material had not reached the expected target. This study aims to determine the relationship between study habits and learning outcomes in Single Choreography in the Traditional Choreography course at the Dance Education Study Program, University of Lampung. This research employed a quantitative approach with a correlational design. The sample consisted of 54 students from the 2022 cohort. Data collection techniques included a study habits questionnaire based on indicators proposed by Slameto (2010: 82) and documentation of learning outcome scores. The data were analyzed using the Pearson Product Moment correlation test with the assistance of SPSS. The results showed a significance value of 0.000 (<0.05) with a correlation coefficient of 0.612, which falls into the strong relationship category. These findings indicate that there is a significant relationship between study habits and learning outcomes in Single Choreography. Therefore, study habits play an important role in improving students’ learning outcomes in Single Choreography learning.